2017
DOI: 10.17503/agrivita.v39i3.1454
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Dioxide Gas Retain Postharvest Quality and Shelf Life of Tomato during Modified Atmosphere Packaging Storage

Abstract: While surface sterilization can minimize the postharvest loss of fruits and vegetables, it depends on concentration, treatment duration, storage condition, and crops. This study was conducted to investigate the consequences of chlorine dioxide (ClO 2 ) gas on post-harvest quality and shelf life of tomato fruits during the modified atmosphere packaging storage. Tomato fruits of light red maturity stage were harvested at Gangwon province in the Republic of Korea. Fruits were dipped in fungal suspension and, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Firmness was also maintained during 4 °C storage (Table 2). Tese results are in agreement with previous reports: Islam et al [13] reported that 12 h of gaseous ClO 2 treatment can yield tomatoes with greater frmness. Similarly, ClO 2 delayed the softening of grape tomatoes [25], and a ClO 2 self-releasing sheet was efective in maintaining the frmness of cherry tomatoes [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Firmness was also maintained during 4 °C storage (Table 2). Tese results are in agreement with previous reports: Islam et al [13] reported that 12 h of gaseous ClO 2 treatment can yield tomatoes with greater frmness. Similarly, ClO 2 delayed the softening of grape tomatoes [25], and a ClO 2 self-releasing sheet was efective in maintaining the frmness of cherry tomatoes [26].…”
Section: Discussionsupporting
confidence: 93%
“…ClO 2 exposure positively afects the composition of volatile compounds and free amino acids in citrus fruits, resulting in the retention of their distinct favors [11]. ClO 2 exposure retains the titratable acidity (TA), soluble solid content (SSC), and vitamin C content in tomato and mulberry [12,13]. In another study, the sensory properties of plums were preserved upon ClO 2 treatment [14].…”
Section: Introductionmentioning
confidence: 95%
“…However, Mahmoud et al (2007) found that 5 mg L −1 ClO 2 treatment did not influence the exterior color and visual appearance of strawberries at 4°C after 16 days. Similarly, Islam et al (2017) said that 5 mg L −1 ClO 2 gas treatment of tomatoes for 12 h maintained their skin color and freshness.…”
Section: Fruitsmentioning
confidence: 99%
“…For example, delayed senescence in ClO 2 -treated longan fruit has been reported to be associated with an altered redox state and increased cellular energy ( Chumyam et al, 2016 ). Moreover, reduced microbial incidence in ClO 2 treated produce leads to quality retention and shelf-life extension ( Islam et al, 2017 ).…”
Section: Modes Of Chlorine Dioxide Actionmentioning
confidence: 99%